Synthesis of Carbon Nanocapsules and Nanotubes Using Fe-Doped Fullerene Nanowhiskers - Tokushi Kizuka; Kun'ichi Miyazawa; Daisuke Matsuura (Journal of Nanotechnology)
We synthesized iron-(Fe-)doped C60 nanowhiskers (NWs) by applying the liquid-liquid interfacial precipitation method that employs a C60-saturated toluene solution and a solution of 2-propanol containing ferric nitrate nonahydrate (Fe(NO3)3⋅9H2O). Fe particles of 3–7 nm in diameter were precipitated in the NWs. By heating at 1173 K, the NWs were transformed into hollow and Fe3C-encapsulated carbon nanocapsules and carbon nanotubes.